PERCEPTION OF FARMERS AND NON-FARMERS AROUND BUI NATIONAL PARK TOWARD THE MANAGEMENT OF PROBLEM WILDLIFE. (Journal of Science and Technology, 2016)
Farmers and non-farmers in 10 fringe communities around Bui National Park were surveyed to examine perceptions of human-wildlife conflicts and their management. Participatory Rural Appraisal (PRA) and Rapid Rural Appraisal (RRA) tools were used to gather information. The response groups tended to attribute different degrees of depredation to certain wildlife species. In choosing control methods to manage wildlife conflicts, both farmer and non-farmer groups tended to prefer lethal methods. Most farmers (84.0%) and non-farmers (68.3%) believed baboons were the most severe or frequent source of crop depreciation followed by bush fowl and patas monkey in descending order of severity of depredation. Approximately 86.0% of farmers and 72.0% of non-farmers felt hunting reduced the depredation-related problems, but non-farmers were approximately three times as likely as farmers to prefer non-lethal control techniques for warthogs. The fact that there is no disparity in perceptions of crop depredation wildlife makes it easier for development of a management plan for the park. On the contrary, the existence of disparities in perceptions of control techniques for depredation wildlife is a potential source of conflict in the development of a management plan for Bui National Park. However, residents of fringe communities of the park agreed to suggested use of non-lethal means of control only if they would be compensated for crop and livestock losses. Local people also suggested their involvement in the protection and management of the park.